Ultrafast tryptophan-to-heme electron transfer in myoglobins revealed by UV 2D spectroscopy - Consani, Cristina; Auböck, Gerald; van Mourik, Frank; Chergui, Majed (Science (American Association for the Advancement of Science), 2013)
Tryptophan is commonly used to study protein structure and dynamics, such as protein folding, as a donor in fluorescence resonant energy transfer (FRET) studies. By using ultra-broadband ultrafast two-dimensional (2D) spectroscopy in the ultraviolet (UV) and transient absorption in the visible range, we have disentangled the excited state decay pathways of the tryptophan amino acid residues in ferric myoglobins (MbCN and metMb). Whereas the more distant tryptophan (Trp(7)) relaxes by energy transfer to the heme, Trp(14) excitation predominantly decays by electron transfer to the heme. The excited Trp(14)→heme electron transfer occurs in <40 picoseconds with a quantum yield of more than 60%, over an edge-to-edge distance below ~10 angstroms, outcompeting the FRET process. Our results raise the question of whether such electron transfer pathways occur in a larger class of proteins.